Manfaat Diet Vegetarian Bagi Obesitas - Aulia Latifah Azzahra (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Nutritional problems such as obesity warrant serious attention, due to their potential to contribute to various other health complications. One modifiable factor associated with obesity that can be targeted through intervention is dietary pattern, including adoption of vegetarian diet. Several previous studies have suggested that vegetarian diets may be effective in promoting weight loss. This study aims to examine the potential role of vegetarian diets in the management of obesity. The method employed in a literature review of relevant studies published within the last ten years. The findings indicate that vegetarian diets are effective in reducing body weight, insulin resistance, blood glucose levels, trimethylamin N-oxide (TMAO), low-density lipoprotein (LDL), triglycerides (TG), and total cholesterol levels. Additionally, they are associated with increased high-density lipoprotein (HDL) levels and improvements in lipid profiles, as well as kidney and liver function. Nevertheless, the implementation of vegetarian diets among individuals with obesity should be carefully supervised and planned by qualified professionals to minimize the risk of nutritional deficiencies.